Investigating the interactions between DNA and DndE during DNA phosphorothioation. Issue 19 (27th July 2019) - Yao, Penfei; Liu, Yaping; Wang, Chengkun; Lan, Wenxian; Wang, Chunxi; Cao, Chunyang
Abstract : The DNA phosphorothioate modification is a novel physiological variation in bacteria. DndE controls this modification by binding to dsDNA via a mechanism that remains unclear. Structural analysis of the wild‐type DndE tetramer suggests that a positively charged region in its center is important for DNA binding. In the present study, we replaced residues G21 and G24 in this region with lysines, which increases the DNA binding affinity but does not affect the DNA degradation phenotype. Structural analysis of the mutant indicates that it forms a new tetrameric conformation and that DndE interacts with DNA as a monomer rather than as a tetramer. A structural model of the DndE–DNA complex, based on its structural homolog P22 Arc repressor, indicates that two flexible loops in DndE are determinants of DNA binding Abstract :